Membangun Guru Inovatif: Sinergi Kepemimpinan Melayani, Iklim Sekolah, dan Semangat Berprestasi - Febriany Sakina Tinambunan; Iyan Irdiyansyah; Nita Karmila (Didaktika: Jurnal Kependidikan, 2025)
Innovative behavior is a person's action in exploring problems, developing, promoting, and realizing new ideas in the form of processes, products, or procedures to improve work effectiveness for the benefit of the organization. This study aims to determine whether there is a direct or indirect influence of the variables of servant leadership, organizational climate, and achievement motivation on teachers' innovative behavior. This research is a quantitative study using a survey method and a path analysis approach. The population in this study consists of teachers with civil servant status (PNS) at public elementary schools in South Bogor District, Bogor City. A sample of 145 teachers was selected using a proportional random sampling technique from a population spread across 37 public elementary schools in South Bogor District, Bogor City. The results of the study show a direct positive influence between: (1) Servant leadership on innovative behavior (β=0.133); (2) organizational climate on innovative behavior (β=0.116); (3) achievement motivation on innovative behavior (β=0.733); (4) servant leadership on achievement motivation (β=0.438); (5) organizational climate on achievement motivation (β=0.198); (6) there is a positive indirect effect of servant leadership on innovative behavior through achievement motivation with an effect value of 0.321; (7) there is a positive indirect effect of organizational climate on innovative behavior through achievement motivation with an effect value of 0.145. The results of the study indicate that innovative behavior can be enhanced through servant leadership, organizational climate, and achievement motivation. Keyword: achievement motivation, innovative behavior, organizational climate, servant leadership